Uso de antibióticos convencionais e antimicrobianos a base de lúpulo no controle da infecção bacteriana em fermentação alcoólica - Prado, Josimara Lacerda [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (EIA Energy in Agriculture, 2014)
The aim of this work was to compare the efficiency of conventional antibiotics in relation to hop-based antimicrobials, in industrial-scale bioethanol production. The comparison was made by calculating the lactic acid bacteria population reduction in two consecutive fermentation cycles. To conduct the experiment, it was used five treatments (three conventional antibiotics: Kamoran WP, Corstan and Alcapen 1030, and two hop-based antimicrobials: BetaBio and IsoStab). The samples were collected in the fermentation vat. In order to quantify the initial lactic acid bacteria population, a sample was collected at the end of the fermentation process (wine) before the treatment with antibiotics or antimicrobials, and to determine the final population, another sample was collected at the end of the fermentation process (wine) after the treatment with antibiotics or antimicrobials. The experiment was completely randomized and the statistical analysis was performed through analysis of variance (ANOVA) for data processed using the equation y’ = . After the data transformation, the Levene's test was applied to verify data adherence to normal distribution, and the averages were compared through Tukey’s test at 5% probability. The results showed that the hop-based antimicrobials (IsoStab and BetaBio) can be used to substitute the conventional antibiotics (Kamoran, Alcapen and Corstan), since there was no statistical difference between the treatments.

O objetivo deste trabalho foi comparar a eficiência de antibióticos convencionais em relação aos antimicrobianos à base de lúpulo, em escala de produção industrial de bioetanol. A comparação foi feita por meio de cálculo da redução populacional de bactérias láticas em dois ciclos consecutivos de fermentação. O experimento teve cinco tratamentos (três antibióticos convencionais: Kamoran WP, Corstan e Alcapen 1030, e dois antimicrobianos à base de lúpulo: BetaBio e IsoStab). As amostras foram coletadas na dorna de fermentação. Para quantificar a população inicial de bactérias láticas, foi coletada amostra no final do processo fermentativo (vinho) antes do tratamento com antibióticos ou lúpulo, e para determinar a população final, a coleta das amostras foi realizada ao final do processo fermentativo (vinho) após o tratamento com esses produtos. O experimento foi inteiramente casualizado e a análise estatística foi realizada por meio da análise de variância (ANOVA) para as variáveis transformadas pela equação y’ = . Após a transformação dos dados foi aplicado o teste de Levene para verificar a aderência dos dados á distribuição normal, e as médias comparadas por meio do teste de Tukey em nível de 5% de probabilidade. Os resultados mostraram que os antimicrobianos a base de lúpulo (IsoStab e Beta Bio) podem substituir os antibióticos convencionais (Kamoran, Alcapen e Corstan), pois não houve diferença estatística entre os tratamentos.
Use of conventional antibiotics and hop-based antimicrobial in control of alcoholic fermentation bacterial infection
Keywords: Alcohol; Sugar cane; Lactic acid bacteria; Contaminants; Álcool; Cana; Bactérias láticas; Contaminantes.